Is there a “weekend effect” in major trauma? - Metcalfe, D; Perry, D; Bouamra, O; Salim, A; Lecky, F; Woodford, M; Edwards, A; Costa, M (BMJ Publishing Group, 2016)
Background Many previous studies have shown that patients admitted to hospital at weekends have worse outcomes than those on other days. It has been proposed that parity of clinical services throughout the week could mitigate the “weekend effect”. This study aimed to determine whether or not a weekend effect is observed within an all-hours consultant-led major trauma service. Methods We undertook an observational cohort study using data submitted by all 22 Major Trauma Centres (MTCs) in England to the Trauma and Audit Research Network (TARN). The inclusion criteria were all major trauma patients admitted for at least three days, admitted to a high dependency area, or deceased following arrival at hospital. Patients with Injury Severity Score (ISS) >15 were also analysed separately. The outcome measures were length of stay, in-hospital mortality, and Glasgow Outcome Score (GOS). Secondary transfer of patients between hospitals was also included as a process outcome. Results There were 49,070 patients, 22,248 (45.3%) of which had an ISS >15. Within multivariable logistic regression models, odds of secondary transfer into an MTC were higher at night (adjusted OR 2.05, 95% CI 1.93-2.19) but not during the day at weekends (1.09, 0.99-1.19). Neither admission at night nor at the weekend was associated with increased length of stay, worse GOS, or higher odds of in-hospital death. These findings remained stable when confining analyses to the most severely injured patients (ISS >15), excluding transferred patients, and using a single mid-week (Wednesday) baseline. Conclusions After adjustment for known confounders the weekend effect is not detectable within a regionalised major trauma service.